2017
DOI: 10.1113/jp275369
|View full text |Cite
|
Sign up to set email alerts
|

Axonal GABAA receptors depolarize presynaptic terminals and facilitate transmitter release in cerebellar Purkinje cells

Abstract: In neurons of the adult brain, somatodendritic GABA receptors (GABA Rs) mediate fast synaptic inhibition and play a crucial role in synaptic integration. GABA Rs are not only present in the somatodendritic compartment, but also in the axonal compartment where they modulate action potential (AP) propagation and transmitter release. Although presynaptic GABA Rs have been reported in various brain regions, their mechanisms of action and physiological roles remain obscure, particularly at GABAergic boutons. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 54 publications
(74 reference statements)
7
39
0
Order By: Relevance
“…Simulation demonstrated that the action potential of nearby MFBs (108.2 mV in amplitude) was passively propagated to the next MFBs (17.3 mV in amplitude). The spatial distribution constant of the passive propagation of transient signal, which we defined in this study as the distance that reduced the size of the transient signal to 1/e (37%) without any active conductance, was estimated as 53.6 µm, and this value was similar with that reported for Purkinje cell axons ( Zorrilla de San Martin et al, 2017 ). Therefore, the capacitive component of ADP may reflect the propagation of action potentials at upstream axons and/or MFBs.…”
Section: Resultssupporting
confidence: 78%
“…Simulation demonstrated that the action potential of nearby MFBs (108.2 mV in amplitude) was passively propagated to the next MFBs (17.3 mV in amplitude). The spatial distribution constant of the passive propagation of transient signal, which we defined in this study as the distance that reduced the size of the transient signal to 1/e (37%) without any active conductance, was estimated as 53.6 µm, and this value was similar with that reported for Purkinje cell axons ( Zorrilla de San Martin et al, 2017 ). Therefore, the capacitive component of ADP may reflect the propagation of action potentials at upstream axons and/or MFBs.…”
Section: Resultssupporting
confidence: 78%
“…We hypothesized that the most likely neuronal compartments rendering GtACR2 excitatory were the distal axon and presynaptic terminals because of the following previous findings. First, activation of presynaptic GABA A or glycine receptors enhanced neurotransmitter release at several synapses of the hippocampus, cerebellum, and brainstem ( Jang et al, 2006 ; Pugh and Jahr, 2011 ; Ruiz et al, 2010 ; Stell et al, 2007 ; Turecek and Trussell, 2001 ; Zorrilla de San Martin et al, 2017 ). Second, the chloride concentrations were 4–5 times higher in the presynaptic terminals of the Calyx of Held than the parent soma ( Price and Trussell, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated, the excitatory action of chloride channels in the axon and presynaptic terminals is due to the high intracellular chloride concentrations that create a depolarizing chloride electrochemical gradient. The depolarizing effect of presynaptic chloride channels, GABA A or glycine receptors, has been documented at a few synapses in the hippocampus, cerebellum, and brainstem through application of agonists or antagonists ( Jang et al, 2006 ; Pugh and Jahr, 2011 ; Ruiz et al, 2010 ; Stell et al, 2007 ; Turecek and Trussell, 2001 ; Zorrilla de San Martin et al, 2017 ). Our results in cortical excitatory and inhibitory neurons expand previous findings and indicate that a presynaptic depolarizing chloride electrochemical gradient is likely a general property across brain regions and neuronal types.…”
Section: Discussionmentioning
confidence: 99%
“…Local activation of AMPA-type glutamate receptors on CA3 pyramidal axons has been shown to broaden the action potential and increase synaptic transmission [46 ]. In a similar way, GABA released by cerebellar interneurons or by Purkinje cells has been shown to depolarize their axon terminals locally [47] and this depolarization associated with incoming action potentials promote GABA release [19 ]. GABA also exerts specific action on presynaptic terminals in glutamatergic neurons.…”
Section: Analog-digital Signaling In the Axonmentioning
confidence: 98%
“…It led to the emergence of the concept of hybrid Analog-Digital modulation of synaptic transmission in mammalian axons in which the shape of the action potential considered as a digital signal is modulated by the analog context in which it is triggered [13][14][15][16]. Moreover, the presynaptic voltage-gated Ca 2+ channels (Cav) opening is steeply dependent on action potential waveform [17] and, at both glutamatergic and GABAergic terminals, vesicle fusion is supralinearly dependent on Ca 2+ entry [18,19 ]. Therefore, the spike shape can exert a strong impact on neurotransmission [20].…”
Section: Analog-digital Signaling In the Axonmentioning
confidence: 99%